2012
DOI: 10.1007/s00167-012-2140-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence after Bankart repair a systematic review

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
179
4
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 39 publications
7
179
4
7
Order By: Relevance
“…7,9,10,16 Other risk factors include male sex, older age, greater time from first dislocation to surgery, and participation in a competitive level of sports. 17,18 In our review, however, the most common reason for failed primary stabilization procedures requiring revision surgery was a repeat traumatic event. Similarly, other studies have shown this to be a predominant factor for failure, occurring in 34% to 96% of patients.…”
Section: Discussionmentioning
confidence: 84%
“…7,9,10,16 Other risk factors include male sex, older age, greater time from first dislocation to surgery, and participation in a competitive level of sports. 17,18 In our review, however, the most common reason for failed primary stabilization procedures requiring revision surgery was a repeat traumatic event. Similarly, other studies have shown this to be a predominant factor for failure, occurring in 34% to 96% of patients.…”
Section: Discussionmentioning
confidence: 84%
“…Although Witney-Lagen et al [32] reported a one-suture anchor fixation technique, their purse-string technique was not used in the present case series. Randelli et al [24] also reported that the use of less than three anchors is significantly associated with recurrent instability. Griesser et al [14,15] reported that glenoid rim fracture after the Latarjet procedure can be treated conservatively.…”
Section: Number Of Anchorsmentioning
confidence: 99%
“…The lead article of this issue of the journal focuses on risk factors that might cause failure after Bankart repair and summarizes the articles published in peer-reviewed journals over the last 10 years [7]. Interesting findings are reported, but most of these studies present level IV evidence.…”
mentioning
confidence: 99%
“…There are many advantages of using arthroscopic techniques, such as minimizing surgical trauma, less pain after surgery, addressing additional pathologies, and-not to be forgotten-cosmetic aspects. Interestingly, Randelli et al [7] found that using less than three anchors for stabilization showed significant increase in recurrence rate. Four or more anchors appear to be even safer in terms of lower redislocation rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation